Multi-Dimensional Molecular Regulation of Trichome Development in Arabidopsis and Cotton - Wang, Yanan; Zhou, Qi; Meng, Zhigang; Abid, Muhammad Ali; Wang, Yuan; Wei, Yunxiao; Guo, Sandui; Zhang, Rui; Liang, Chengzhen (Frontiers in Plant Science, 2022)
Plant trichomes are specialized epidermal cells that are widely distributed on plant aerial tissues. The initiation and progression of trichomes are controlled in a coordinated sequence of multiple molecular events. During the past decade, major breakthroughs in the molecular understanding of trichomes development were achieved through the characterization of various trichomes defective mutants and trichomes-associated genes, which revealed a highly complex molecular regulatory network underlying plant trichomes development. This review focuses on the recent millstone in plant trichomes research obtained using genetic and molecular studies, as well as ‘omics’ analyses in model plant Arabidopsis and fiber crop cotton. In particular, we discuss the latest understanding and insights into the underlying molecular mechanisms of trichomes formation at multiple dimensions, including at the chromatin, transcriptional, post-transcriptional, and post-translational levels. We summarize that the integration of multi-dimensional trichomes-associated genes will enable us to systematically understand the molecular regulation network that landscapes the development of the plant trichomes. These advances will enable us to address the unresolved questions regarding the molecular crosstalk that coordinate concurrent and ordered the changes in cotton fiber initiation and progression, together with their possible implications for genetic improvement of cotton fiber.